Reflections on strategies for university supervision in special education - Bussey, Heidi; Lay, Celina Dulude (Frontiers in Education, 2023)
University supervisors for special education teachers are preparing teacher candidates to have many roles and responsibilities and to collaborate with many stakeholders, even as they begin their field experiences. In this self-study of teaching and teacher educator practice, we examined the narrative reflections of a university professor in her role as a university professor and supervisor for special education student teachers. Our narrative data revealed: individualized strategies for supporting the supervision of special education student teachers; how these tools emerged directly from background, experience, theory, and beliefs; the value of relationships in university supervision; and, reflection as a diagnostic tool for improving practice and identifying teacher educator knowledge.